2010
DOI: 10.1126/science.1178068
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Deglacial Overturning and Water Mass Source Changes

Abstract: Understanding changes in ocean circulation during the last deglaciation is crucial to unraveling the dynamics of glacial-interglacial and millennial climate shifts. We used neodymium isotope measurements on postdepositional iron-manganese oxide coatings precipitated on planktonic foraminifera to reconstruct changes in the bottom water source of the deep western North Atlantic at the Bermuda Rise. Comparison of our deep water source record with overturning strength proxies shows that both the deep water mass so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
315
2
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(352 citation statements)
references
References 33 publications
32
315
2
3
Order By: Relevance
“…Indicators of vertical variability of the water mass boundary between NSW and SSW have been detected in carbon isotope time series and records of other proxies at various locations in the North Atlantic (Oppo and Lehman, 1995;Zahn et al, 1997;Hagen and Keigwin, 2002;Rasmussen et al, 2003;Peck et al, 2007b), as well as in NW Atlantic Nd isotope records shown here and previously (Gutjahr et al, 2008;Roberts et al, 2010). Based on benthic foraminiferal assemblages, Rasmussen et al (2003) suggested the presence of relatively warm, poorly ventilated and nutrient rich deep water akin to water of southern origin during Heinrich Events in the southeast Labrador Sea and the presence of NADW in between.…”
Section: Shallowing Of Northern Deep Watersmentioning
confidence: 90%
See 3 more Smart Citations
“…Indicators of vertical variability of the water mass boundary between NSW and SSW have been detected in carbon isotope time series and records of other proxies at various locations in the North Atlantic (Oppo and Lehman, 1995;Zahn et al, 1997;Hagen and Keigwin, 2002;Rasmussen et al, 2003;Peck et al, 2007b), as well as in NW Atlantic Nd isotope records shown here and previously (Gutjahr et al, 2008;Roberts et al, 2010). Based on benthic foraminiferal assemblages, Rasmussen et al (2003) suggested the presence of relatively warm, poorly ventilated and nutrient rich deep water akin to water of southern origin during Heinrich Events in the southeast Labrador Sea and the presence of NADW in between.…”
Section: Shallowing Of Northern Deep Watersmentioning
confidence: 90%
“…Bayon et al, 2002;Piotrowski et al, 2005;Gutjahr et al, 2007). A major deglacial shift of 3e43 Nd units towards more radiogenic signatures of bottom waters in deep NE and NW Atlantic core sites was interpreted as increased presence of Southern Source Water during the LGM and the deglaciation (Gutjahr et al, 2008;Yu et al, 2008;Roberts et al, 2010). In the deep NE Atlantic, radiogenic 3 Nd signatures as high as À8.4 during the LGM changed towards less radiogenic values as low as À11.2 during the early Holocene (Yu et al, 2008).…”
Section: Water-mass Tagging By Nd Isotopesmentioning
confidence: 96%
See 2 more Smart Citations
“…Given that Nd has an average global oceanic residence time of ∼ 400-700 yr (Rempfer et al, 2011) and differences in ε Nd between water masses are large enough to be detectable (cf. Frank, 2002), Nd isotopes have been used as a quasi conservative tracer to infer changes in past deep-water sources and their mixing within the North Atlantic basin on different timescales (e.g., O'Nions et al, 1998;Burton et al, 1999;Roberts et al, 2010;Crocket et al, 2011;Piotrowski et al, 2012). .…”
Section: Introductionmentioning
confidence: 99%